Pelatihan dan penerapan agrosilvo konservasi mendukung pertanian organik berkelanjutan di Desa Aunupe Kabupaten Konawe Selatan Provinsi Sulawesi Tenggara [Training and application of agrosilvo conservation supports sustainable organic farming in Aunupe Village, South Konawe Regency, Southeast Sulawesi] - Kahirun, Kahirun; Kandari, Aminuddin Mane; Erif, La Ode Muhammad; Kete, Surya Cipta Ramadhan (Buletin Pengabdian, 2024)
The agricultural practices carried out by the people of Aunupe Village have been going on for several generations, but the agricultural system used is not optimal because they still use a conventional farming system, namely monoculture. Apart from that, the agricultural input used is chemical fertilizer which of course does not meet the organic aspect and is not sustainable, because high chemical input and long use can damage the texture and nutrients of the soil. For this reason, community empowerment through training in the application of organic farming techniques in the form of agrosilvo conservation in an agroforestry pattern needs to be encouraged so that local communities who use land in forest areas not only obtain agricultural products but can also benefit from environmental and economic services so that they can be sustainable. Thus, the appropriate alternative that can be implemented is to utilize a non-timber farming system combined with maintaining wood trees, known as an agroforestry system, namely agrosilvo conservation. This service aims to provide knowledge and examples to the farming community regarding how to cultivate agriculture using a combination of non-timber plants and woody plants, namely with the conservation agrosilvo system. The method used is descriptive qualitative. The results of the PKMI program activities are the socialization of agro-silvoconservation activities and increased knowledge and capacity of the community in carrying out farming using the agrosilvo-conservation method.